Implementasi Program Kerja Kegiatan Kampus Mengajar Batch 1 Di SMK Negeri 5 Palangka Raya - Ginting, Ravael; Sihombing, Dedi Jupiter (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Campus Teaching Program (Kampus Mengajar) is designed to support students in their learning and facilitate their adaptation to technological developments, literacy, and numeracy. The goal of the Batch 1 Campus Teaching Program is to provide support to teachers and staff in developing student potential and improving school quality. This program includes approaches and training in the use of technology, such as red tilapia fish hatchery and pond water neutralizers, and Microsoft Excel training. The method applied in the Batch 1 Campus Teaching Program uses a qualitative approach. Various achievements from the Batch 1 Campus Teaching Program include the creation of a reading corner, planting and constructing shelves for medicinal plants, helping repair the school nameplate and updating the school's writing, conducting literacy and numeracy activities, making trash bins, repairing/remaking ceremonial equipment, practicing Monday and other important day ceremonies, cleaning and painting the pond behind the school, constructing hydroponic plant shelves, developing activities through joint worship services with students, numeracy training on Microsoft Excel, providing technology training in pond water neutralizer techniques, and red tilapia fish hatchery.